Efektivitas Penggunaan Aplikasi Youtube dalam Media Pembelajaran Berbasis ICT (Information and Communication Technology) pada Siswa Kelas XI SMA Nurul Hasanah Ciheulang - Trikawati Trikawati; Euis Ismayati Yuniar; Yulaikah Yulaikah; Kety Soraya; Machron Chairulfalah; Lia Nurliana; Fifi Musfirowati (Badan Penerbit STIEPARI Press, 2025)
This research aimed to explain the effectiveness of using the YouTube application in based learning media on ICT (Information and Communication Technology). The research method used was descriptive qualitative which aimed to obtain in-depth information about the effectiveness of using the YouTube application in ICT-based learning media for class XI students of SMA Nurul Hasanah Ciheulang Lebak Banten through participatory observation, interviews, and documentation. Through the Miles and Huberman data analysis techniques, researchers collected and reviewed existing data, performed data reduction, data presentation, and concluded it. The research results were that teachers could display interesting, interactive, and fun learning videos, became a medium for self-expression and foster creativity in students in practicing teaching materials, and learning could be accessed anytime and anywhere without being limited by space or time.